Analysis of Related Technical Problems of RCCD Ultra-long Core Samples Based on Huangdeng Hydropower Station - HU Hongxia (Renmin Zhujiang)
For the 24.6 m of the world's longest roller compacted concrete coresamples taken out during the quality inspection of RCCD (roller compacted concretedam) at Huangdeng Hydropower Station, in order to better analyze and summarize theexperience of roller compacted concrete construction technology and constructionmanagement experience, combined with the results of concrete mixing test, revisionof construction specifications, inter-layer binding technology, temperature andcrack control technology and construction management measures, this paper analyzesthe performance and related technical problems of the ultra-long core sample andconcrete, and suggests that the acquisition of ultra-long core samples is directlyrelated to the quality of raw concrete materials, mix ratio, uniformity andworkability of concrete mixture, inter-layer binding properties, mechanicalproperties, volume stability, anti-cracking performance and constructionmanagement measures. It is shown that the raw concrete materials selected duringthe construction of RCCD at Huangdeng Hydropower Station are of good quality,reasonable mix ratio, uniform quality of mixture, good concrete workability,inter-layer binding performance, mechanical properties and anti-crackingperformance, and proper temperature and crack control and construction managementmeasures.